Innovative Advanced Footstep-Based Power Generation and Energy Harvesting System - R Nandhagopal,; J Krishna Kumar,; B S Jameelur Rahman,; S Magesh Kannan,; B Sachin,; M Suthan, (International Journal of Scientific Research in Science and Technology, 2025)
The global push toward sustainable energy has led to innovative methods of harvesting energy from everyday activities. This paper explores an advanced footstep power generation system utilizing piezoelectric sensors in conjunction with IoT components for efficient energy management.The system employs piezoelectric sensors embedded in flooring to capture mechanical energy from footsteps, converting it into electrical energy.This footstep power generation system offers a low-cost, environmentally friendly solution for energy harvesting in high-footfall areas such as malls, airports, and public walkways. The combination of RFID technology and real-time data displays enhances user engagement and system monitoring, making it a promising approach for smart city applications and energy efficiency optimization.
Keywords: power generation; piezoelectric sensor electricity generation; low cost; electrical energy; footsteps; renewable energy